2016
DOI: 10.1093/annonc/mdv543
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling identifies responsive patients with cancer of unknown primary treated with carboplatin, paclitaxel, and everolimus: NCCTG N0871 (alliance)

Abstract: NCT00936702.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 28 publications
0
58
0
Order By: Relevance
“…As reviewed by Moran et al, a handful of clinical trials have evaluated the impact of TOO-prediction based site-specific treatment with regards to improved clinical outcome (36). In a small prospective phase II trial, Yoon et al successfully molecularly profiled the TOO of 38 out of 45 confirmed CUP patients with a 2000-gene expression microarray-based assay (41). All of these patients were treated with carboplatin, paclitaxel and everolimus.…”
Section: Chasing the Tissue Of Origin (Too) In Cupmentioning
confidence: 99%
“…As reviewed by Moran et al, a handful of clinical trials have evaluated the impact of TOO-prediction based site-specific treatment with regards to improved clinical outcome (36). In a small prospective phase II trial, Yoon et al successfully molecularly profiled the TOO of 38 out of 45 confirmed CUP patients with a 2000-gene expression microarray-based assay (41). All of these patients were treated with carboplatin, paclitaxel and everolimus.…”
Section: Chasing the Tissue Of Origin (Too) In Cupmentioning
confidence: 99%
“…Bone metastasis from cancer of unknown primary (BMCUP) is defined as a heterogeneous group of biopsy‐proven metastatic bone cancers for which no primary lesion can be detected by thorough diagnostic evaluation, accounting for 10% of all cancer types . BMCUP has very poor prognosis, with roughly 6 to 9 months of survival, not only because of failure to detect or cure primary cancer, but also due to oncological heterogeneity and histological biomarkers, which makes surgical, systemic or target therapies difficult …”
mentioning
confidence: 99%
“…Histological markers were detected in known primary tumors treated with sunitinib, including RCC, and studies on mouse models and RCC patients demonstrated antitumor effect of sunitinib against skeletal metastatic RCC through inhibition of osteoclast function, but there were few investigations on survival‐associated histological biomarkers on CUP, probably owing to heterogeneity of the occult primary site . BMCUP requires special attention, not only because of its diminished life quality or survival prognosis, but also several studies demonstrated that bone metastasis was independently associated with poor outcome for patients with CUP in general …”
mentioning
confidence: 99%
See 2 more Smart Citations